Respuesta :
The equivalent equation is [tex](x+5)(x+12)=0[/tex]
The solution are [tex]x=-5, x=-12[/tex]
Explanation:
Given that the equation is [tex]-7 x-60=x^2+10 x[/tex]
Simplifying the equation, we get,
[tex]0=x^2+10 x+7x+60[/tex]
Switch sides, we have,
[tex]x^2+17 x+60=0[/tex]
Equivalent equation:
Let us factor the quadratic equation.
Thus, we have,
[tex]x^{2} +5x+12x+60=0[/tex]
Grouping the terms, we get,
[tex]x(x+5)+12(x+5)=0[/tex]
Factoring out (x+5), we get,
[tex](x+5)(x+12)=0[/tex]
Thus, the equivalent equation is [tex](x+5)(x+12)=0[/tex]
Solution:
Solving the equation [tex](x+5)(x+12)=0[/tex], we get,
[tex]x+5=0[/tex] and [tex]x+12=0[/tex]
[tex]x=-5[/tex] and [tex]x=-12[/tex]
Thus, the solutions are [tex]x=-5[/tex] and [tex]x=-12[/tex]
Answer:
A. 5
B. 12
C. -12 or -5
Step-by-step explanation:
(x + 5)(x + 12) = 0
What are the solutions of –7x – 60 = x2 + 10x?
x = -12 or -5